2023
DOI: 10.1055/a-2043-1044
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin is a Key Factor for Nonalcoholic Fatty Liver Disease in Obese Children

Abstract: This study investigates whether serum prolactin (PRL) is a key factor for nonalcoholic fatty liver disease (NAFLD) in children. A total of 691 obese childred participated in this study and were divided into a NAFLD group (n=366) and simple obesity (SOB) group (n=325) according to the hepatic ultrasound results. The two groups were matched for gender, age, pubertal development, and body mass index (BMI). All patients underwent an OGTT test, and fasting blood samples were collected to measure prolactin. Stepwise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Another study by Shao et al [26] found that hepatic TG accumulation could be reduced in female mice, and liver steatosis could be alleviated in male mice when given PRL in a high-fat diet-induced NAFLD model. Considering that a decrease in PRL has been observed in NAFLD patients of both genders [24,27], whether there are sexual differences between serum PRL and NAFLD remains unknown. During this study, we observed a weak correlation between sex hormones and ALT (Supplementary Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Another study by Shao et al [26] found that hepatic TG accumulation could be reduced in female mice, and liver steatosis could be alleviated in male mice when given PRL in a high-fat diet-induced NAFLD model. Considering that a decrease in PRL has been observed in NAFLD patients of both genders [24,27], whether there are sexual differences between serum PRL and NAFLD remains unknown. During this study, we observed a weak correlation between sex hormones and ALT (Supplementary Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…The study of Zhang et al [ 1 ] exhibits a signifi cant selection bias, which should have been addressed. It is not understandable, why patients with hyperprolactinemia were excluded from the study population, when prolactin levels are the main factor under investigation.…”
Section: Dear Editormentioning
confidence: 99%
“…
Dear Editor,The authors thank the writers [1] of the letter for reviewing and assessing our article [2], "Prolactin is a Key Factor for Nonalcoholic Fatty Liver Disease in Obese Children". Overall, we agree that possible selection bias must be considered.
…”
mentioning
confidence: 99%
“…Hyperprolactinemia was used as an exclusion criterion in the study. According to the Chinese consensus on hyperprolactinemia diagnosis and management 3 , hyperprolactinemia is a clinical diagnosis based on a comprehensive analysis of clinical manifestations and serum prolactin levels. Clinical manifestations usually include galactorrhea in girls, breast development, and tumor masses in boys.…”
mentioning
confidence: 99%